The Study of Syntactic Error Review of Editorial News Titled Politics is Getting Hotter - Efendi*, Erwan; Hermaya, Azzahra Putri; Ferina, Lisa; Surya, Surya (Riwayat: Educational Journal of History and Humanities, 2023)
The background of this research is the discovery of errors in the Indonesian language in online news writing. The most obvious error is at the syntax level. Therefore, this study aims to explain the form of language errors in the field of syntax contained in the online news portal Sindonews in the editorial news text entitled "Politics Getting Hot". This study uses a qualitative method with a descriptive approach. To obtain data, the observation technique was chosen as a data collection method. Furthermore, the data were analyzed using the distribution method. The results of the research regarding the analysis of language errors in the field of syntax contained in the editorial news include errors in coherence, borrowed words, sentence effectiveness, unity, and sentence logic that do not match. This study reinforces the paradigm that online news portals ignore the principles of Indonesian language syntax.